2008
DOI: 10.1002/ejoc.200800018
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Metal‐Catalyzed N‐Heteroarylation and C–C Cross‐Coupling Reactions: An Expedient Route to Tris(hetero)aryl Systems

Abstract: This paper describes copper‐catalyzed N–C heteroarylation of benzimidazole, 1‐methylbenzimidazolone, imidazole and pyrrole. The products of these reactions then undergo palladium‐catalyzed C–C cross‐couplings with aryl or heteroarylboronic acids under Suzuki–Miyaura conditions to provide a rapid entry, from readily‐available reagents, into tris(hetero)aryl scaffolds comprising two or three N‐heterocyclic rings. The sequential N–C and C–C couplings can be performed in a one‐pot process (two examples are given: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Rh-, Ru-and Pd-based noble metal complexes with a large number of phosphorous [3,4] , carbene [5][6][7] , oxime [8,9] , imine [10][11][12] and other ligands [13,14] have been reported as catalysts for such couplings. From an academic, industrial, and economic standpoint, the abundant and inexpensive use of copper has led to remarkable progress in the development of copper-catalyzed C-C and C-N bond formation reactions [15][16][17][18][19] . Buchwald et al [20] and Taillefer et al [21][22][23] revealed rate accelerations when arylations were conducted in the presence of certain copper ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Rh-, Ru-and Pd-based noble metal complexes with a large number of phosphorous [3,4] , carbene [5][6][7] , oxime [8,9] , imine [10][11][12] and other ligands [13,14] have been reported as catalysts for such couplings. From an academic, industrial, and economic standpoint, the abundant and inexpensive use of copper has led to remarkable progress in the development of copper-catalyzed C-C and C-N bond formation reactions [15][16][17][18][19] . Buchwald et al [20] and Taillefer et al [21][22][23] revealed rate accelerations when arylations were conducted in the presence of certain copper ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Unsymmetric terphenyls and disubstituted pyridines have been prepared through double Suzuki−Miyaura reactions by using different arylboronic acids . Very recently, the sequential copper-mediated C−N and subsequent Pd-catalyzed C−C couplings of aryl dihalides were also known to give tris(hetero)aryl compounds . To achieve high regioselectivity, double couplings of the dihaloarene equivalents have been explored.…”
mentioning
confidence: 99%
“…Such a route has been applied for the synthesis of liquid crystal materials via sequencial Negishi/Still couplings . However, some reported sequential coupling reactions suffer disadvantages such as requirement of two different catalysts, the intermediate products have to be separated prior to the second coupling, or using not easily available substrates. ,, From the viewpoint of efficiency, one-pot sequential reactions of commercially available inexpensive aryl dihalides with a single catalyst are desirable, and so far only a few successful examples have been reported. ,, …”
mentioning
confidence: 99%
See 1 more Smart Citation